FILSAFAT ALKINDI DALAM PERSPEKTIF AL-QUR'AN - Yulia Latifah; Sabilla Azzahra HR; Tri Isma Adi Putra; Devi Silvian Quraeny (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2021)
Philosophy and religion are two things that complement each other. Philosophy that deviates from thought and religion that deviates from belief has caused many people to criticize the existence of philosophy that can shake beliefs. In the eighth century, Al-Kindi emerged as the first Muslim philosopher who created the continuity of philosophy and religion, both philosophy and religion adhering to the truth. The most noble of al-Kindi's philosophy is the First Philosophy, which is to work hard to know the First God, namely Allah. Al-Kindi's sacred philosophy is included in the scope of metaphysics. In proving the existence of God, Al-Kindi put forward an empirical argument. They are: the new nature post (Hudutsil alam), the diversity post (Kastrah fil Maujudat) and the control nature post (Ibda'fil Alam). In addition, in the Qur'an there is also the word "God" is used to refer to gods other than Allah, such as idols, lust, gods. However, the word "Allah" is a special name that is not owned by any other word besides Him, because only God Almighty who must exist has the right to use this name, and no one or even should not except Him. The reality of the real existence of the Qur'an uses all forms as evidence, especially the existence of this universe and everything in it. This article uses the previous literature method, the aim is to understand the various meanings of Al-Kindi's divinity by referring to the Qur'an.